The influence of pulse-plasma treatment on the phase composition and hardness of Fe-TiB2-CrB2 coatings - Kengesbekov, A; Rakhadilov, B. K.; Tyurin, Yu. N.; Magazov, N. M.; Kylyshkanov, M. K.; Sagdoldina, Zh.B. (Eurasian Journal of Physics and Functional Materials, 2026)
This work are presented the research results of pulse plasma treatment influence on the phase composition, hardness, roughness and element composition of coatings on the bases of Fe-TiB2-CrB2. The Fe-TiB2-CrB2 coatingwas depositedby detonation method. The following pulse-plasmatreatment was used to modify the structure and properties of the surface layers of the sprayed coating. The results of mechanical experiments showed that the hardness of Fe-TiB2-CrB2 coating increased after the treatment. On the basis of the X-ray analysis, it has been established that the increase of coating hardness is connected with phase transformations in a surface layer, in particular, with formation of oxide phases and increase of carbide particles quantity.Recommended CitationKengesbekov, A. B.; Rakhadilov, B. K.; Tyurin, Yu. N.; Magazov, N. M.; Kylyshkanov, M. K.; and Sagdoldina, Zh. B. (2021) "The influence of pulse-plasma treatment on the phase composition and hardness of Fe-TiB2-CrB2 coatings," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 2, Article 9.DOI: https://doi.org/10.32523/ejpfm.2021050209